The first mitochondrial genome from the Sterrhinae (Lepidoptera: Geometridae) and its phylogenetic implications. Issue 1 (2nd January 2020) - Song, Lu; Shi, Yu-Xia; Li, Jun-Hao; Su, Si-Lin; Zhang, Hong-Fei; Ding, Wei-Li; Yang, Ming-Sheng
Abstract: In this study, the complete mitochondrial genome of a geometrid species, Idaea simplicior (Prout), was sequenced. The I. simplicior mitogenome is a circular, double-stranded molecule, with 15, 950 bp in size. The typical 37 mitochondrial genes (13 PCGs, 22 tRNAs, and 2 rRNAs) and an A + T-rich region are included. Gene content and arrangement are highly conserved and typical of Lepidoptera. Interestingly, the I. simplicior mitogenome is rich in microsatellite sequences of (TA)12–18 with a scattered distribution in six intergenic regions. Phylogenetic analyses based on the combined 37 mitochondrial genes show that the Larentiinae and Ennominae are monophyletic. The Sterrhinae, which is represented by the only I. simplicior sequenced in this study, shows a closer relationship with the Larentiinae than Ennominae, which confirms previous morphological studies.